Public Relations Strategy of Sekolah Islam Terpadu (SIT) Auliya Bintaro in Maintaining Consumer Loyalty - Sembodo, Agung Priyo; Swarnawati, Aminah (International Journal of Social Service and Research, 2023)
Educational institutions must carry out Public Relations (PR) strategies but cannot be separated from businesses such as the Sekolah Islam Terpadu (SIT) Auliya Bintaro. The Customer Division carries out the PR strategy to reach its consumers, namely the Muslim middle class. The study aimed to find out 1) SIT Auliya Bintaro's PR strategy in maintaining consumer loyalty 2) Obstacles to SIT Auliya Bintaro's PR strategy in maintaining consumer loyalty. RACE (Research, Analysis, Communication, and Evaluation) is the theory used. This research method uses case studies with a qualitative approach. Data collection techniques through in-depth interviews and literature studies. Selection of informants as many as 3 people by purposive means. The results showed that SIT Auliya's Customer Division runs its communication programs by the four-step process of strategic PR management, namely RACE, with findings of the application of PR through Cyber, which is indicated to maintain consumer loyalty. The online tools studied are Instagram, websites, and WhatsApp. The obstacles encountered stem from the lack of human resources and adequate facilities and infrastructure to carry out PR strategies through Cyber, the search for content materials in the field, and problems that can cause complaints from consumers.